(untitled) (Annals of Medical Research, 2024)
Aim: Taxifolin (dihydroquercetin) is a natural bioactive flavonoid with antifungal, antiviral, antibacterial, antioxidant, and anti-inflammatory properties, and is a valuable compound in the medical, pharmaceutical, and food industries. This study aims to determine the Minimum Inhibitory Concentration (MIC) of pure taxifolin (99.25%) against pathogenic and opportunistic microorganisms. Materials and Methods: The antibacterial and antifungal activities of taxifolin against two Gram-positive (E. aerogenes, S. aureus), three Gram-negative (P. aeruginosa, K. pneumonia and E. coli), and four yeast strains (C. krusei, C. glabrata, C. tropicalis and C. albicans) was determined using agar and broth microdilution methods. Results: The MIC value for tested Gram-positive bacteria is 1 mg/mL, which is 2 mg/ml for Gram-negative bacteria. At the same time, the MIC value was 8 mg/mL for all Candida species tested except C. glabrata (MIC: 4 mg/mL). Conclusion: In conclusion, it was determined that the antibacterial property of taxifolin was more pronounced than its antifungal properties. Taxifolin is a natural compound with high medical and pharmacological value. This study proved the effectiveness of pure taxifolin as a pharmacotherapeutic agent on pathogenic and opportunistic microorganisms. The preliminary data collected in this study should be further supported, and in vivo and bioavailability studies should be detailed in future studies.